Narrative Review: Pembelajaran Zat Aditif Pada Sabun Cuci Piring Berbasis Project Based Learning (PJBL) Dalam Kurikulum Merdeka Pada Siswa SMP - Erika Utami Erika; Magfira Ramadani; Nur Azizah Ashara Putri; Puput Habri Anugrah; Ramlawati Ramlawati (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
Learning about additives in science in junior high schools requires a contextual approach so that students can understand the concepts and their application in everyday life. This study aims to assess the effectiveness of implementing Project-Based Learning (PjBL) in learning about additives through a dishwashing soap-making project within the Independent Curriculum. The study used a literature review method with a narrative review design, analyzing 20 national articles published between 2018 and 2025, obtained through Google Scholar. The results showed that the implementation of PjBL improved students' conceptual understanding, critical thinking skills, creativity, learning motivation, and science process skills. The dishwashing soap-making project also provided a more contextual learning experience and fostered entrepreneurial skills and awareness of the safe use of chemicals. Despite several constraints such as limited time and resources, the PjBL model was deemed effective in learning about additives for junior high school students, in accordance with the requirements of the Independent Curriculum.